"The Mill on the Floss" - the critique of the concept of education in Victorian Great Britain - Ninčetović, Nataša V. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
George Eliot was not only a significant Victorian writer, but primarily an intellectual. She thought that literature had an important role in the reform of society, the moral and educational function. Eliot interwove her views on the direction in which the society should move in her works, so that the analysis of her opus cannot be separated from the social circumstances in Victorian Great Britain. The aim of this work is to imply at the fact that by means of The Mill on the Floss George Eliot indirectly criticized the official concept of education of the Victorian era. The starting point of our research is an overview of the state of society, followed up by George Eliot’s attitudes towards the question of education, which can be found in her essays and letters. The Mill on the Floss is a picturesque illustration of George Eliot’s beliefs that education should be reformed, as well as of the need of a different approach to this extremely important question. The implication of this novel is that education needs to be appropriate to the requisites and competences of the student, but also that education mustn’t be reduced to a commodity, so that we should raise the awareness that education has a much more important and wider role than mere acquisition of a degree and means that will faciliate easier employment.